Improving Collaborative Learning and Performance in Industrial Training: An Approach to Multiplayer Virtual Reality Serious Games - Miranda, Arthur Spinassé; Ferreira, João Vitor Ladislau; Lazarini, Thales Pinheiro; De Angeli Neto, Alexandre; Novais, Matheus Gianordoli; Andreão, Rodrigo Varejão; Schmidt, Marcelo Queiroz; Mestria, Mário (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais Estendidos do XXVII Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2025.15382, 2025)
Virtual Reality (VR) has become a key platform for serious games, especially in high-risk industries that require immersive and safe training. Although single-player simulations help with individual development, they are insufficient to develop team skills such as communication and coordination. This paper presents a multiplayer VR serious game that transforms individual training into a collaborative experience. The multiplayer approach improves both technical mastery and interpersonal skills, including cooperation and situational awareness. Research shows that this model increases engagement, satisfaction, and performance. By addressing challenges such as latency and social interaction, the study offers a more effective method for industrial training in virtual collaborative environments.